ANALISIS YURIDIS PELAKSANAAN PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) PROGRAM KERJA TAHUN 2017-2018 pada Kantor Pertanahan Kota Medan - FANNI DAMARA ARIF (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING: 1. Muhd Yamin 2. Syafruddin Kalo 3. SaidinIn order to provide the insurance of legal certainty and protection for people’s land justly and equally, and to encourage national economic growth and people’s economy in particular, it is necessary to conduct accelerated complete land registration in all parts of the Republic of Indonesia. PTSL (Complete Systematic Land Registration) is a program conducted by the Ministry of Agrarian Affairs and Spatial Planning/ Head of Indonesian National Land Office to increase the number of land registration and certificate issuance in Indonesia. The conduct of this program is stipulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/ Head of Indonesian National Land Office No. 6/2018 on Complete Systematic Land Registration. In practice, there are some obstacles encountered in its implementation; thus, some field target planning in a region cannot be achieved. The research discusses the legal regulations of the conduct of accelerated PTSL, PTSL as accelerated land registration, and its implementation in Medan.Keywords: Land Registration, Complete Systematic Land Registration, Policy and Solution